The second cataract fortress of Dorginarti - Heidorn, Lisa A. 1956- (Nubian Expedition, 2023)
"The best-known sites along the length of the Nile River's Second Cataract are the ruins of Egyptian towns and fortresses occupied during the Old, Middle, and New Kingdoms. The fortresses were part of Egypt's lines of defense and facilitated trade in this region. Trade, military, and cultural contacts existed between Egypt and Nubia throughout history because many desired commodities-raw materials and animal and plant products-stemmed from lands under Kushite control or beyond to the south, east, and west. Although shipping via the Red Sea and the long haul through the western desert became more common from the later first millennium BC on, the Nile remained a vital conduit regardless of which state or tribal power controlled the regions along it. One of the fortresses in the Second Cataract region, Dorginarti existed in a later era than the better-known Middle and New Kingdom forts. The earliest ceramics found at the site date from the later tenth or early ninth century BC, and those from a later occupation stem from the early eighth century. The latest phase of occupation did not extend far beyond the first phase of Persian dominance in Egypt beginning in the last quarter of the sixth century BC. This volume is the final report of the emergency excavations undertaken at Dorginarti for five months in 1964 by the University of Chicago's Oriental Institute as part of the UNESCO Nubian salvage project necessitated by the building of the Aswan High Dam. Following a description of the fortress's landscape and resources, the book describes Dorginarti's architecture in detail and then presents the selection of artifacts brought back from the Sudan and stored in the Oriental Institute Museum. The picture that emerges from the archaeological record shows the continuing importance of Lower Nubia after the withdrawal of Egyptian control in the late second millennium BC and before the rise of the Kushite empire in the Twenty-Fifth Dynasty"-- Provided by publisher